Preservação e Conservação - a Situação nas Bibliotecas e Arquivos em Portugal - Neves, Almira; Matos, Susana (Cadernos BAD, 1991)
Preservação e Conservação - a Situação nas Bibliotecas e Arquivos em Portugal